Analisis Minat Masyarakat Non Muslim Tentang Perbankan Syariah dari Tahun ke Tahun di Indonesia - Faisal Fahmi; Muhammad Habibi Siregar (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Islamic banks in terms of their current development are not lagging behind with progress as well as conventional ibanks. Conventional ibanking ithat iimplements ian iinterest isystem igoes iside iby iside iwith iIslamic ibanking ithat iimplements ia iprofit-sharing isystem. iThe iproblem ifaced iby iIslamic ibanks iis ithe ilow ipublic iknowledge iabout iIslamic ibanking, iespecially icaused iby ithe idominance iof iconventional ibanking iso ithat iIslamic ibanking iis istill iunderestimated. iThe ipurpose iof ithis istudy iis ito ifind iout ihow ithe ipublic iunderstands iIslamic ibanking iin iAdi iJaya iVillage, iFlygi iBesar iDistrict, iCentral iLampung iRegency. iThis itype iof iresearch iis ifield iresearch iconducted iin iKampung iAdi iJaya. iThe inature iin ithis istudy iis ia iqualitative idescriptive imethod. iThere iare itwo isources iof idata iin ithis istudy, inamely iprimary idata isources iand isecondary idata isources. iThe iprimary idata isource iis iobtained idirectly ifrom ithe icommunity, iwhile ithe isecondary idata isource ithat ithe iresearchers iuse iis iin ithe iform iof iKampung iAdi iJaya idocuments iand ifrom ivarious ibooks. iTo iobtain ivalid idata, iresearchers iuse ia idata icollection imethod, inamely iinterviews. iAfter ithe idata iis icollected, ithe iresearcher ianalyzes iusing iqualitative idata ianalysis itechniques iusing iinductive imethods.. iThe iresults iof ifield iresearch ishow ithat ithe iunderstanding iof ithe ipublic iabout iIslamic ibanks iin iKampung iAdi iJaya iis ithat ipeople ionly iknow ithe iexistence iof iIslamic ibanks ibut ido inot iunderstand iIslamic ibanks iin idetail. iOnly isome ipeople iunderstand iabout iIslamic ibanks iand isome ieven idon't iknow iabout iIslamic ibanks iat iall. iMost ipeople ido inot iknow iwhat iproducts iand iservices iare iavailable iin iIslamic ibanks. iLack iof iunderstanding ifrom ithe ipublic idue ito ithe ilack iof iinformation iobtained ifrom iIslamic ibanks iand imedia isuch ias itelevision, iprint imedia iand isocial imedia iwhich icauses ipeople inot ito iknow iwhat iIslamic ibanks iare iand iwhat iproducts iare iin I Islamic ibanks.